D Penetapan Kadar Flavonoid Total Ekstrak Daun Kapuk Randu (Ceiba pentandra (L.) Gaertn) berdasarkan Tingkatan Fraksi: Penetapan Kadar Flavonoid Total Ekstrak Daun Kapuk Randu (Ceiba pentandra (L.) Gaertn) berdasarkan Tingkatan Fraksi - Hesty Wulandari; Rohama Rohama; Putri Vidiasari Darsono (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: Kapok leaf (Ceiba pentandra (L.) Gaertn) is a plant that grows a lot in Central Kalimantan which is empirically used as an inhibitot of kidney stone formation and can shed kidney stones. Kapok leaves are known to contain flavonoids that can inhibit formation and dissolving kidney stones. Objective: To determine the total flavonoid content of kapok leaf extract in the n-hexane, ethyl acetat and methanol fractions. Methods: Observational descriptive method by looking at the results of the data, qualitative by using color reaction test and thin layer chromatography (TLC) and quantitative data by using UV-Vis spectrophotometry to see the total levels of flavonoids. Results: The result of qualitative analysis of flavonoid compounds with color reactions and TLC showed that they contained flavonoid compounds positive. The results of quantitative analysis using UV-Vis spectrophotometric showed that the total flavonoid content in the ethanol extract 96%, n-hexane fraction, ethyl acetate fraction and methanol fraction respectively were 31,663 mg QE / g or 3,1667%; 5,167 mg QE / g or 0,5167%; 51,833 mg QE / g or 5,1833%; and 7,166 mg QE / g or 0,7166%. The highest total flavonoid content was in the ethyl acetate fraction. Conclusion: The kapok leaf extract with the fraction level contains flavonoid compounds with total flavonoid content in the ethanol extract 96%, n-hexane fraction, ethyl acetate fraction and methanol fraction respectively were 31,663 mg QE / g or 3,1667%; 5,167 mg QE / g or 0,5167%; 51,833 mg QE / g or 5,1833%; and 7,166 mg QE / g or 0,7166%.